Smart Parachute Broadcloth Fabrics Using Weaved Distributed Fiber Optic Sensors - Mendoza, Edgar; Prohaska, John; Mendoza, Sebastian; Antreas, Theodore; Esterkin, Yan; Theodosiou, Antreas; Kalli, Kyriacos; Kelsay, Connor; Lowry, Charles; Tutt, Ben; Hill, Peter; Willey, Nicola; et al. (My University, 2022)
The research work presented in this paper describes progress steps by our collaborating group geared towards the automated production of Smart parachute broadcloth fabrics instrumented with weaved fiber optic sensors suitable for monitoring the load and strain dynamics of a parachute canopy during airborne deployment, and the subsequent methodology use for the fabrication assembly of down-scale test parachutes used for testing the aerodynamic properties of the parachute during ejection and descend of the parachute canopy structure. The fiber optic sensors are woven into the broadcloth using various weaving methods to find the most consistent and repeatable response to stress and strain in the cloth. This research has focused on the use of plastic optical fiber strain sensors that have almost identical elongation properties to the parachute canopy Nylon broadcloth fabrics for which they will impregnate. Experimental results on the Smart parachute fabrication assembly, laboratory calibration testing, and the canopy load and strain dynamics during airborne deployment will be demonstrated.
Keywords: Aerodynamics; Aviation; Fiber optics; Optical fiber fabrication; Optical fibers; Parachutes; Weaving